Comparison of mitral valve geometrical effect of percutaneous edge-to-edge repair between central and eccentric functional mitral regurgitation: clinical implications. (9th August 2018) - Utsunomiya, Hiroto; Itabashi, Yuji; Kobayashi, Sayuki; Yoshida, Jun; Ikenaga, Hiroki; Rader, Florian; Hussaini, Asma; Makar, Moody; Trento, Alfredo; Siegel, Robert J; Kar, Saibal; Shiota, Takahiro
Abstract: Aims: Percutaneous edge-to-edge repair alters mitral valve (MV) geometry in functional mitral regurgitation (FMR). We sought to characterize MV morphology in patients with central and eccentric FMR, compare the geometrical effect of MitraClip therapy, and elucidate different mechanisms of MR improvement according to FMR subtypes. Methods and results: Seventy-six symptomatic patients with Grade 3 to 4+ FMR (central, n = 39; eccentric, n = 37) underwent three-dimensional transoesophageal echocardiography during MitraClip implantation. We defined procedural success as a reduction of MR by ≥1 grade with having a residual mitral regurgitation (MR) of ≤ grade 2+. Procedural success rate was similar between central and eccentric FMR (77% vs. 78%, P = 0.55). After MitraClip, the reduction in anterior-posterior diameter did not differ between FMR subtypes, but patients with eccentric FMR had a greater reduction in the averaged tethering angle difference ( P < 0.001) with less reduction in tenting volume and height (both P < 0.001) than did patients with central FMR. On multivariable analysis, in central FMR, MR reduction post-clip was associated with shortening in anterior-posterior diameter [coefficient 0.388, 95% confidence interval (CI) 0.216–0.561; P < 0.001] and an increase in coaptation area (coefficient 0.117, 95% CI 0.039–0.194; P = 0.004), whereas in eccentric FMR MR reduction was mainly associated with a decrease in the averaged tethering angle difference (coefficient 0.050, 95% CI 0.021–0.078; P = 0.001). Conclusion: MV geometrical effect and its association with MR improvement after MitraClip therapy differ according to FMR subtypes. Our results indicate the MR jet direction and the leaflet tethering pattern may be considered in the strategy for percutaneous treatment for FMR.